TINGKAT ADOPSI ELECTRONIC WORD OF MOUTH OLEH PENGIKUT MEDIA SOSIAL INSTAGRAM “KECIPIR” - Stephanie Maria Zerlina Mayang Ken Wuri; Agriani Hermita Sadeli; Sulistyodewi Nur Wiyono (Universitas Galuh, 2023)
The development of the internet resulted in the emergence of new communication channels. This new channel type resulted in an increase eWOM. Often in making purchasing decisions, eWOM is adopted as a consideration for users of information. This study uses the information acceptance model (IACM) to determine the level of adoption of eWOM information by information users. The purpose of this study is to determine the level of adoption of eWOM information by Instagram social media followers engaged in agriculture such as Kecipir. This study uses quantitative methods assisted by Smart PLS with descriptive analysis and convenience sampling techniques. There were 100 respondents to this study who came from Kecipir Instagram followers. The results of the study show that the adoption rate of Ewom by Instagram social media followers is in the very good category.